Defect Structure, Transport Properties, and Chemical Expansion in Ba0.95La0.05FeO3–δ. Issue 3 (18th March 2021) - Bae, Hohan; Singh, Bhupendra; Mathur, Lakshya; Joo, Jong Hoon; Song, Sun-Ju
Abstract : This work systematically investigates the oxygen nonstoichiometry, defect structure and mass/charge transport properties of Ba0.95 La0.05 FeO3− δ (BLF). Thermogravimetric measurement and coulometric titration were performed to determine change in oxygen nonstoichiometry ( δ ) with oxygen partial pressure ( P O 2 ) in 10 −17 ≤ ( P O 2 /atm) ≤ 0.21 and 850 ≤ (T/°C)≤900 range. The δ − P O 2 −T plot showed "S-type" shape with a crossover plateau around δ ≈ 0.475. Defect modelling was used to explain the nonstoichiometry data and partial molar thermodynamic quantities for oxygen were determined. The DC 4-probe conductivity measurement was performed which showed a typical semiconductor-to-metal transition with temperature around the conductivity maxima at 450 °C. Electrical conductivity relaxation (ECR) measurement was performed to extract partial ionic conductivity, chemical diffusivity and surface exchange kinetics of oxygen ion by using Nernst-Einstein equation and Fick's law. Isothermal chemical expansion was measured by dilatometry measurement in the range of 10 −2 ≤ ( P O 2 /atm) ≤ 0.21 and 850 ≤ (T/°C) ≤ 950.